Skin Acts : Race, Psychoanalysis, and the Black Male Performer - Stephens, Michelle Ann (Book collections on Project MUSE., 2014)
In Skin Acts, Michelle Ann Stephens explores the work of four iconic twentieth-century black male performers-Bert Williams, Paul Robeson, Harry Belafonte, and Bob Marley-to reveal how racial and sexual difference is both marked by and experienced in the skin.